2018
DOI: 10.3390/ijerph16010094
|View full text |Cite
|
Sign up to set email alerts
|

Employee Stress, Reduced Productivity, and Interest in a Workplace Health Program: A Case Study from the Australian Mining Industry

Abstract: The Australian mining sector has an elevated industry prevalence of stress and high stress related productivity impairment costs. This study surveyed 897 employees from an Australian mining company to identify characteristics associated with: (a) high stress related productivity impairment costs; and (b) likelihood of stressed employees wanting stress management assistance at work. Groups associated with average annual productivity impairment costs in excess of $50,000 per employee included: permanent day shif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Moreover, it is examined that the higher stress level of employees leads to higher productivity cost. In the same paper, differences between genders also found that female employees were more likely report wanting assistance for stress management than male employees, although females and males show similar average of impairment cost [9].ther research about psychological strain in Hungarian mining industry studied on 71 miners working in 794 shifts across 5 mining plants. The study targeted detailed factors such as presence of managers, temperature of mining site, illumination in mining site and so on, finding these might affect heart rate of miners, which indicates miners' strain.…”
Section: Previous Studiesmentioning
confidence: 91%
“…Moreover, it is examined that the higher stress level of employees leads to higher productivity cost. In the same paper, differences between genders also found that female employees were more likely report wanting assistance for stress management than male employees, although females and males show similar average of impairment cost [9].ther research about psychological strain in Hungarian mining industry studied on 71 miners working in 794 shifts across 5 mining plants. The study targeted detailed factors such as presence of managers, temperature of mining site, illumination in mining site and so on, finding these might affect heart rate of miners, which indicates miners' strain.…”
Section: Previous Studiesmentioning
confidence: 91%
“…Therefore, to spend time for the desired outcome, it is expected that employees will expend effort and have high work engagement by using limited resources, and this is known as work productivity [67]. Previous researchers suggested in their studies that productivity does not have a single operational definition, but it varies according to multifaceted situations and the types of organizations and their cultures [39,68,69]. Worker productivity is integrated with organizational productivity and employee work performance, which determines the quality of work [70].…”
Section: Worker Productivitymentioning
confidence: 99%
“…Companies, as the micro-main body of the market, and the industry have to adapt to climate change [67,68]. Thus, energy-intensive manufacturing undertakes its role in the energy conservation mission and in emission reduction [69][70][71][72].…”
Section: Discussionmentioning
confidence: 99%